Ties and inequalities in later life: welfare state regime and the role of social networks in health inequalities in later life in Europe - Craveiro, D. (European Societies, 2017)
Cross-national comparisons on health inequalities have puzzled health researchers in the last years. Contrary to what is theoretically expected, Northern European countries, known for their advanced welfare state regime and universalistic policies in health and social protection, do not present smaller health inequalities than other European nations. Within the debate triggered by these surprising results, some authors consider the possibility that the differences among the welfare state regimes may be shaping the relevance of specific pathways or mechanisms underlining the association between socioeconomic position (SEP) and health. This research addresses this hypothesis by comparing the contribution of social networks to health inequality in later life across different welfare state regimes. Mediation effects between SEP and health by social networks variables are compared across four different welfare state regimes, using data from Survey of Health, Ageing, and Retirement in Europe. Findings suggest that the socioeconomic advantages in health are partially explained by the differentials in social integration and quality of social ties. Welfare state regimes appear to shape the contribution of social networks in health inequality concerning the implications of the exchanges of social support in health.